2023
DOI: 10.1038/s41586-023-05842-x
|View full text |Cite
|
Sign up to set email alerts
|

An infrared transient from a star engulfing a planet

Abstract: It is well known that planets with short orbital periods (≲ 10 days) are common around stars like the Sun 1-3 . Stars expand as they evolve, and thus we expect their close planetary companions to be engulfed [4][5][6] . However, this phase has never been directly observed. Here, we present the discovery of ZTF SLRN-2020, a short-lived optical outburst in the Galactic disk accompanied by bright and long-lived infrared emission. The resulting light curve and spectra share striking similarities with those of red … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 126 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…Punzi et al (2018) suggested that the hot gas revealed from the optical spectroscopy could originate from the accretion of material from a hot Jupiter-like planet swallowed by the star. The aftermath of such an engulfment might have been observed recently in ZTF SLRN-2020 (De et al 2023). If true, the detailed evolution of the hot gas in RZ Psc might provide an additional test bed for such a phenomenon.…”
Section: The Origin Of the Gas Reservoirmentioning
confidence: 80%
“…Punzi et al (2018) suggested that the hot gas revealed from the optical spectroscopy could originate from the accretion of material from a hot Jupiter-like planet swallowed by the star. The aftermath of such an engulfment might have been observed recently in ZTF SLRN-2020 (De et al 2023). If true, the detailed evolution of the hot gas in RZ Psc might provide an additional test bed for such a phenomenon.…”
Section: The Origin Of the Gas Reservoirmentioning
confidence: 80%
“…McQuillan et al (2013) find a dearth of close-in planets orbiting rapidly rotating stars, which Teitler & Königl (2014) attribute to tidal ingestion of giant planets. The recently reported infrared transient ZTF SLRN-2020 appears to capture the moments of a planet's ingestion by a main sequence or early subgiant branch star with mass around 0.8-1.5M e , and could be the culmination of tide-induced orbital decay (De et al 2023).…”
Section: Introductionmentioning
confidence: 96%
“…The rapid rotation reported for HJ hosts may also be a signature of stellar spin-up associated with orbital decay, i.e., angular momentum transfer from the orbit to spin (e.g., Penev et al 2018;Tejada Arevalo et al 2021). Even the detection of an infrared transient associated with the engulfment of a shortperiod planet has been reported (De et al 2023). Of particular relevance to our paper is the work by Hamer & Schlaufman (2019), who showed that Sun-like stars known to host HJs have a smaller Galactic velocity dispersion than their control stars without known planets, and those with known cold Jovian planets.…”
Section: Introductionmentioning
confidence: 99%